2018
DOI: 10.1007/s00414-018-1926-1
|View full text |Cite
|
Sign up to set email alerts
|

Dental age estimation in Somali children using the Willems et al. model

Abstract: The WM and SM were similar in their age prediction performances, and the use of the WM in dental age assessment in the Somali population is justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A previous study of the same Somali sample [44], comparing Willems model using Belgian Caucasian population [58] and the constructed Somali model, provided support for the universal application of the Willems model for forensic age estimation, since only small differences in age prediction performances were detected between the two models.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A previous study of the same Somali sample [44], comparing Willems model using Belgian Caucasian population [58] and the constructed Somali model, provided support for the universal application of the Willems model for forensic age estimation, since only small differences in age prediction performances were detected between the two models.…”
Section: Discussionmentioning
confidence: 84%
“…Studies on the dental development in sub-Saharan populations and in Somalis, indigenous to Northeast Africa, are few, however [ 12 , 41 , 47 ]. Recently, permanent tooth development has been studied in the South-African Black population [ 46 ], in Botswanan children [ 40 ], and in Somali children born in Finland [ 44 ]. Studies of third molar development in sub-Saharan populations were also recently published on South African [ 35 , 43 , 48 50 ], Sudanese [ 20 ], Kenyan [ 45 ], Botswanan [ 51 ], Nigerian and Senegalese individuals [ 35 ], and on Northeast Africans from Libya [ 52 ], Morocco [ 53 ] and Sudan [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Willems et al found that the overall MAE was slightly higher with the Willems BC method than with a South African-specific method in black children (0.68 years vs. 0.62 years) [ 18 ]. However, Cadenas de Llano-Pérula et al and Metsäniitty et al found that the overall MAE was same the Willems BC method [ 31 , 32 ]. Our result shows that the overall MAE to be slightly higher when using the Willems BC method than when using the Willems SA method (1.37 years vs. 1.33 years) and that the MAE was the same in boys and girls (1.37 years).…”
Section: Discussionmentioning
confidence: 99%
“…The age prediction performance of the Demirjian method has been validated in Spain [ 13 ], Tunisia [ 14 ], France [ 15 , 16 ], Malaysia [ 17 ], and other countries [ 4 , 10 , 16 , 18 ], leading to an overestimation of CA. The Willems method simplifies the transformation steps of the Demirjian method, creating a new table.…”
Section: Introductionmentioning
confidence: 99%
“…The Willems method simplifies the transformation steps of the Demirjian method, creating a new table. It showed that, as tested in different populations, including Somali [ 16 ], South Australian [ 18 ], Navi Mumbai [ 19 ], and Malaysian [ 20 ], the accuracy of estimating DA was consistently higher than that of the Demirjian method [ 21 , 22 ]. Ethnic differences are thought to be a significant factor in the development of dental maturity [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%